"I'm not different, I'm still a human being […] but I am different." An exploration of the experiences of transgender prisoners using interpretative phenomenological analysis. Issue 2 (10th April 2019) - Nulty, Joanne E.; Winder, Belinda; Lopresti, Sally
Abstract : Purpose: The treatment and placement of transgender individuals within the UK prison system has garnered considerable political and media attention. The purpose of this paper is to present an analysis of the experiences of three transgender women located within a male, category C prison in England. Design/methodology/approach: Participants were interviewed and their accounts analysed using interpretative phenomenological analysis. Findings: Three overarching themes emerged from the data set: participants' experiences of transition; their identity within custody and the challenges associated with presenting as female within a male establishment; and what they perceived as their fight against the prison system which encompassed a fight for their rights alongside a daily struggle against harassment, victimisation and discrimination. Research limitations/implications: Three participants were interviewed which impacts the generalisability of the findings. Implications link to the care and management of transgender prisoners. Practical implications: The care and management of transgender prisoners is a complex issue. This paper contributes to the discussion on how best to support and care for this group of service users who are arguably amongst the most vulnerable within the prison system. Social implications: Findings are discussed in relation to policy, management and safeguarding of transgender prisoners within the UK prison system. Recommendations are made regarding their placement and management in prison. Originality/value: There are limited accounts from transgender prisoners regarding their experiences in prison. This paper aims to address that gap.